1998
DOI: 10.1209/epl/i1998-00310-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of a new spin cluster topology with high-spin ground state: the spin cluster [Mn II 4 Mn III 3 (teaH) 3 (tea) 3 ](ClO 4 ) 2

Abstract: The new spin cluster [MnII4MnIII3(teaH)3(tea)3](ClO4)2×3MeOH realizes a topological structure of mixed-valence manganese clusters which is especially favorable for a high-spin ground state. The magnetic properties of the spin cluster are studied numerically by exact diagonalization of the spin Hamiltonian. By magnetic susceptibility two exchange constants are found: J1/kB = − 1.28 K and J2/kB = + 4.25 K, which lead to a S = 11 high-spin ground state. Electron spin resonance (ESR) measurements at three frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1
1

Year Published

1999
1999
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 13 publications
2
38
1
1
Order By: Relevance
“…Other experiments at lower temperature, still in progress, are required to speculate further on this point. The preexponential factor is much shorter than that observed in Mn12 (4) and in another cluster comprising manganese(III) and manganese(IV) ions showing slow relaxation of the magnetization at low temperature (2).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Other experiments at lower temperature, still in progress, are required to speculate further on this point. The preexponential factor is much shorter than that observed in Mn12 (4) and in another cluster comprising manganese(III) and manganese(IV) ions showing slow relaxation of the magnetization at low temperature (2).…”
Section: Resultsmentioning
confidence: 63%
“…Under this respect manganese clusters (2) have been found to be particularly appealing after it was shown that the magnetization of the dodecanuclear cluster [Mn O (CH COO) (H O) ], Mn12Ac, which has a ground S"10 state (3), relaxes very slowly at low temperature (3). In fact, at 2 K the relaxation time of the magnetization is on the order of some months, (4) …”
Section: Introductionmentioning
confidence: 99%
“…High‐frequency EPR (HF‐EPR) spectra : A more detailed investigation of single‐ion anisotropies in 2‐doped was based on HF‐EPR spectroscopy. HF‐EPR represents an unrivaled technique for investigating the ZFS in paramagnetic transition metal complexes, with recent outstanding results in the field of high‐spin molecules 4, 9a, 10a,10b,10g,10h, 11f. Compared to magnetometry techniques it provides information on the local environment of the metal ions, rather than a crystal average.…”
Section: Resultsmentioning
confidence: 99%
“…For example, clusters with highspin ground states were found to represent superparamagnets. [5][6][7] In several clusters macroscopic quantum effects like quantum tunneling of the magnetization were observed. 2,3,[8][9][10][11] A Mn 12 cluster compound was even found to form a molecular magnetically bistable nanomagnet, 12 with an accordingly large technological impact.…”
Section: Introductionmentioning
confidence: 99%